Beyond Memorization: Enhancing Vocabulary Acquisition through Google Sites in Bilingual Pesantren Education - Murtadho, Muhammad Alfa Choirul; Muhammad, Awan Teduh; Taufik; Taqiyudin, Ahmad; Baihaqi, M. (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Vocabulary acquisition in Arabic as a foreign language within pesantren-based educational contexts continues to face persistent challenges due to the dominance of rote memorization practices that inadequately support deep semantic processing, long-term retention, and communicative readiness. This study aims to examine the pedagogical role of Google Sites–based digital instruction in moving beyond memorization by facilitating meaningful lexical processing, learner engagement, and vocabulary retention among students at SMP Bilingual Terpadu Pesantren Modern Al-Amanah Junwangi, Krian. Adopting a qualitative descriptive design, the study employed semi-structured interviews, classroom observations, and document analysis, involving 25 students and 5 Arabic language teachers. The findings indicate that the integration of Google Sites enhanced vocabulary retention through structured, multimodal, and contextualized content presentation, enabling deeper semantic processing compared to conventional memorization-based methods. The platform also contributed to increased learner motivation and affective engagement. However, the data reveal that students’ spontaneous oral use of newly learned vocabulary remained limited and did not develop optimally. This suggests that while Google Sites effectively supports vocabulary retention and emerging readiness for use, full communicative acquisition requires sustained pedagogical mediation and integration with oral interaction practices. The study concludes that Google Sites–based digital instruction functions effectively as a supportive tool for Arabic vocabulary learning beyond mechanical memorization, yet its success is contingent upon teacher scaffolding and alignment with communicative language teaching principles. This research provides empirical insights into digital Arabic pedagogy in bilingual pesantren settings and recommends further investigation into long-term learning outcomes and the integration of digital platforms with productive language use.